Task-oriented training effect on promoting motor skills and daily physical activities in learners with musculoskeletal impairment - Baygaliev, Adilbek; Butabayeva, Laura; Autayeva, Akbota; Eszhanov, Zhaisan; Nishanbayeva, Sabira (Journal of Education and e-Learning Research, 2024)
Children frequently suffer from motor impairments which hinder their development. Every movement requires stability therefore; musculoskeletal malfunction leads to poor movement. Task-oriented training is one of many methods and techniques used to promote motor skills and daily physical activities in children. The present study's goal is to investigate how task-oriented training contributes to developing motor skills and daily physical activities in learners with cerebral palsy. The study employed a mixed- data collection strategy. The study included a total of 12 students with cerebral palsy. The promotion of a child's motor abilities and regular physical activity can be accomplished with the help of task-oriented training. The study's findings supported our hypothesis that task-oriented training that has been devised and a series of exercises to increase range of motion (flexibility) led to positive dynamics in all groups of indicators regardless of the severity of the pathology. The proposed program allowed children to increase muscle strength and range of motion in the joints. Thus, after the experimental work, the functional state of the musculoskeletal system improved and qualitative and significant changes occurred in the independence of learners. It is suggested that teachers use task-oriented training when instructing school-age children who have this disorder.